Characterizing microRNA editing and mutation sites in Autism Spectrum Disorder - Wu, Xingwang; Yang, Huaide; Lin, Han; Suo, Angbaji; Wu, Shuai; Xie, Wenping; Zhou, Nan; Guo, Shiyong; Ding, Hao; Zhou, Guangchen; Qiu, Zhichao; Shi, Hong; et al. (Frontiers in Molecular Neuroscience, 2023)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder whose pathogenesis is still unclear. MicroRNAs (miRNAs) are a kind of endogenous small non-coding RNAs that play important roles in the post-transcriptional regulation of genes. Recent researches show that miRNAs are edited in multiple ways especially in central nervous systems. A-to-I editing of RNA catalyzed by Adenosine deaminases acting on RNA (ADARs) happens intensively in brain and is also noticed in other organs and tissues. Although miRNAs are widely edited in human brain, miRNA editing in ASD is still largely unexplored. In order to reveal the editing events of miRNAs in ASD, we analyzed 131 miRNA-seq samples from 8 different brain regions of ASD patients and normal controls. We identified 834 editing sites with significant editing levels, of which 70 sites showed significantly different editing levels in the superior frontal gyrus samples of ASD patients (ASD-SFG) when compared with those of control samples. The editing level of an A-to-I editing site in hsa-mir-376a-1 (hsa-mir-376a-1 9 A g) in ASD-SFG is higher than that of normal controls, and the difference is exaggerated in individuals under 10 years. The increased expression of ADAR1 is consistent with the increased editing level of hsa-mir-376a-1 9 A g in ASD-SFG samples compared to normal SFG samples. Furthermore, we verify that A-to-I edited hsa-mir-376a-5p directly represses GPR85 and NAPB, which may contribute to the abnormal neuronal development of ASD patients. These results provide new insights into the mechanism of ASD.